Uji Sitotoksik Ekstrak Buah Phaleria macrocarpa terhadap Sel Kanker Lestari A 549 dan THP-1 - Pertamawati Kartakusumah; Susi Kusumaningrum; Hendig Winarno (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Fruits of Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) has been used to cure various health problems, including empirical treatment for cancer. The therapeutic effect of natural material is related to the chemical compound contains. In fruits of Phaleria macrocarpa, various chemicals are present such as alcaloid, flavonoid saponin, fenol and tannin, which showed anticancer activity, as well as unknown compounds which ones presumably supportive for cancer treatment. An in vitro experiment is therefore set up with the objective of examining the effect of fruit extract on male human lung carcinoma epithelial cells (A-549 cell line) and human peripheral blood leukemia acute cells (THP-1 cell line). Various concentrations: 5, 10, 25, 50 and 100 ppm of fruit extract were evaluated. Observations were made 72 hour after incubating A-549 cells and THP-1 cells in each treatments. The results showed that fruit might inhibit the growth of A-549 cells and THP-1 cells. Inhibitory concentration (LC) of fruit extract after 72 hours of incubation is 9,43 ppm for A-549 cells and 5,36 ppm for THP-1 cells. Inhibitory potential effect of these fruits in THP-1 cells are better than in A-549 cells. The effect might be associated to the active compounds contained in these material.